Hubungan Antara Religiusitas dengan Kecenderungan Bunuh Diri pada Individu Dewasa Awal - Grace Onyzha Krisnandita; Dessi Christanti (Universitas Pahlawan Tuanku Tambusai, 2022)
Individuals at the stage of early adult development can experience severe pressure so that there are some early adult individuals who choose suicide as a problem solving. However, there are many individuals in early adulthood who, despite the stress, do not commit suicide. One of the protective factors that reduce the occurrence of suicidal behavior is religiosity. This study aims to determine the relationship between religiosity and suicidal tendencies in early adult individuals. The method used in this research is quantitative. The research subjects consisted of 1337 participants aged 18-40 years with incidental sampling and snowball sampling techniques. Data were collected using the Suicide Behaviors Questionnaire-Revised (SBQ-R) scale and religiosity scale. Data analysis in this study used SPSS 16.0 with Kendall's Tau-b non-parametric technique and got a significance value of 0.00 with an r value indicating a correlation coefficient of -0.132. So it can be concluded that there is a negative relationship between religiosity and suicidal tendencies in early adult individuals.